Identification and expression of the trehalose-6-phosphate synthase gene family members in tomato exposed to different light spectra - Chen, Zexiong; Lou, Juan (Archives of Biological Sciences, 2017)
Light is the source of energy for plants. Light wavelengths, densities and irradiation periods act as signals directing morphological and physiological characteristics during plant growth and development. To evaluate the effects of light wavelengths on tomato growth and development, Solanum lycopersicum (cv. micro-Tom) seedlings were exposed to different light-quality environments, including white light and red light supplemented with blue light (at ratios of 3:1 and 8;1, respectively). Tomatoes grown under red light supplemented with blue light displayed significantly shorter stem length, a higher number of flower buds and rate of fruit set, but an extremely late flowering compared to white-light-grown plants. To illustrate the mechanism underlying the inhibition of stem growth and floral transition mediated by red/blue light, 10 trehalose-6-phosphate synthase (TPS) genes were identified in tomato, and bioinformatics analysis was performed. qRT-PCR analysis showed that SlTPSs were expressed widely throughout plant development and SlTPS1 was expressed at extremely high levels in stems and buds. Further analysis of several flowering-associated genes and microRNAs showed that the expressions of SlTPS1, SlFT and miR172 were significantly downregulated in tomato grown under red and blue light compared with those grown under white light, whereas miR156 transcript levels were increased. A regulatory model underlying vegetative growth and floral transition regulated by light qualities is presented. Our data provide evidence that light quality strongly affects plant growth and phase transition, most likely via the TPS1-T6P signaling pathway. DOI: 10.2298/ABS160325082C Received: March 25, 2016; Revised: June 13, 2016; Accepted: July 26, 2016; Published online: September 21, 2016 How to cite this article: Chen Z, Lou J. Identification and expression of the trehalose-6-phosphate synthase gene family members in tomato exposed to different light spectra. Arch Biol Sci. 2017;69(1):93-101.